One month prevalence of self–reported musculoskeletal pain syndromes and correlates: Enomesečna prevalenca skeletno–mišične bolečine in vplivi nanjo - Klemenc–Ketiš, Zalika; Kersnik, Janko (Acta Medico-Biotechnica, 2021)
Purpose: The aim of this study was to determine the prevalence of 1 month musculoskeletal pain symptoms in a representative sample of the Slovenian general population and to determine factors associated with the symptoms. Methods: We performed an observational cross–sectional study in June 2011 in a representative sample of 1,002 randomly selected Slovenian citizens, stratified according to gender and age, using a computer–assisted telephone interview method. Results: At least 1 day in the past month, 559 participants (55.7%) experienced musculoskeletal symptoms; 226 participants (22.5%) experienced musculoskeletal symptoms everyday of the past month. Older age, female gender, lower education, lower monthly income, seeking lay advice, seeking medical advice, self–treatment, self–reported mobility problems, problems with self–care, pain, difficulties in daily activities, anxiety and/or depression, employment, retired, and a chronic disease were associated with the presence of musculoskeletal pain during the entire past month. When compared to the remainder of the sample, subjects with musculoskeletal pain had more often mobility problems and more often reported the presence of pain. Conclusion: Musculoskeletal symptoms are very common in the Slovenian general population and present a significant public health problem.